THE PSYCHOLOGY OF ARTISTIC IMAGES AND MOTIFS IN A LITERARY WORK - Guzal Umurova (Sciental Journals Publishing, 2026)
The article examines the psychology of artistic images and motifs as central elements of a literary work that mediate between the author’s inner world, the structure of the text, and the process of artistic perception. It analyzes the psychological mechanisms involved in the formation of images, including perception, memory, imagination, emotion, and unconscious processes. Special attention is given to motifs as recurrent semantic and emotional units that reflect the author’s persistent psychological concerns and connect individual experience with archetypal patterns of culture. The article also addresses the role of the reader in constructing meaning and emphasizes the cognitive and emotional functions of artistic imagery in shaping aesthetic experience and understanding human reality.
Keywords: Psychology of art, artistic image, literary motif, creative process, imagination, unconscious processes, artistic perception, archetype, emotional experience, symbolic meaning